Sunbed use in Germany: trends, user histories and factors associated with cessation and readiness to change. (13th August 2013) - Bock, C.; Diehl, K.; Litaker, D.; Breitbart, E.W.; Greinert, R.; Schneider, S.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Exposure to artificial sources of ultraviolet radiation (UVR) through sunbed use has contributed significantly to rising melanoma rates. The International Agency for Research on Cancer has classified UVR from sunbed use as carcinogenic in humans. The use of sunbeds is widespread in developed countries with prevalence estimates for ever having used sunbeds ranging from 11% to 61%. What does this study add? This is the first study to apply event history analysis to quasilongitudinal data on lifetime sunbed use. Among sunbed users, median sunbed exposure was 180 min per year. The initiation age of sunbed use in Germany has decreased over the past several decades. These findings are significant as they highlight the importance of early intervention.